2009
DOI: 10.1097/grf.0b013e3181a2b3cd
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Dilation in Second-Trimester Abortion

Abstract: Dilation and evacuation, the most common method performed for second-trimester abortion in the United States, requires sufficient cervical dilation to reduce the risk of complications such as cervical laceration or uterine perforation. The cervix may be prepared with osmotic dilators such as laminaria, Lamicel, or Dilapan-S, or with pharmacologic agents such as misoprostol. Dilapan-S and Lamicel achieve their maximum dilation faster than laminaria, making same-day procedures possible. Misoprostol has limited d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…In addition, adolescents have a higher risk for cervical laceration because they usually have small, physiologically immature cervices that are difficult to dilate [20-22]. Another significant problem with current cervical dilators is a lack of control over the rate of dilation – extremely rapid cervical dilation often leads to cervical laceration [23,24]. …”
Section: Discussionmentioning
confidence: 99%
“…In addition, adolescents have a higher risk for cervical laceration because they usually have small, physiologically immature cervices that are difficult to dilate [20-22]. Another significant problem with current cervical dilators is a lack of control over the rate of dilation – extremely rapid cervical dilation often leads to cervical laceration [23,24]. …”
Section: Discussionmentioning
confidence: 99%
“…Hayes and Fox8 have reported that Dilapan-S can be difficult to remove due to entrapment and fragmentation. This problem was not met in the Dilapan-S cohort we studied, which we attribute to our use of the dilators being in graded serial stages over 2 days along with the adjuvant use of high-dosage misoprostol.…”
Section: Discussionmentioning
confidence: 99%
“…The likelihood of cervical trauma can be greatly reduced by cervical preparation with Laminaria or pharmacotherapy prior to TOP [5355]. Up to 3% of second trimester TOP procedures are complicated by cervical trauma [56].…”
Section: Short-term Harmsmentioning
confidence: 99%